Devising techniques for reinforcing glued sausage casings by using different physical methods - Оnishchenko Vyacheslav; Pak , Andrey; Goralchuk , Andrii; Shubina , Lidiia; Bolshakova , Viktoria; Inzhyyants , Samvel; Pak, Alina; Domanova , Olena (Eastern-European Journal of Enterprise Technologies, 2021)
This paper has substantiated the development and rationalization of techniques to manufacture sausage casings from natural raw materials with predefined functional and technological properties. It is noted that the issue related to the rational utilization of intestinal raw materials and the improvement of the production economic profitability could be resolved by implementing effective technologies of glued intestinal sausage casings. The strength has been investigated of the reinforcing seam between the layers of intestinal membranes obtained by such techniques as the local tanning, local thermal coagulation resulting from passing an electric current through wet raw materials, local thermal coagulation due to the arc discharge through dried raw materials. The rational concentration of tannin in tanning solution has been determined, at which it is recommended to make a reinforcing seam on glued intestinal casings by means of local tanning. A value of the breaking load for the reinforcing seam made by using local electric currents has been derived, which is 14 N/m. A 4.7-time increase in the breaking load has been established to occur, compared to the control sample. A value of the breaking load for the reinforcing seam obtained by applying an arc discharge has been found, which is 18 N/m. It was noted that the breaking load had increased compared to the control sample. Working bodies for an installation were designed aimed at reinforcing glued sausage casings by such techniques as local tanning; local thermal coagulation resulting from passing an electric current through wet raw materials; local thermal coagulation as a result of arc discharge through dried raw materials. It is noted that the advantages of techniques for the reinforcement of glued sausage casings are the high breaking load and the effective utilization of raw materials